2018
DOI: 10.22201/fca.24488410e.2018.1441
|View full text |Cite
|
Sign up to set email alerts
|

Purchase intention of ethnic textiles: The mediating role of the attitude of Mexican middle-class consumers

Abstract: <p>This research analyzes how behavioral attitude mediated the relationship between ethnical identity and intention to purchase ethnic textiles. We selected a sample of 405 postgraduate students from five different universities who fulfilled the following criteria: (1) they belong to the Mexican middle-class with an income ranging from 479 to 638 dollars a month; (2) they are part of the potential consumer market because they are under 30 years-old on average; and (3) they are familiar with the dynamic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Rahman and Kharb [36] found that fashion innovativeness is particularly valued by young consumers when purchasing clothing. Furthermore, handcrafted products that incorporate ethnic identities and cultural symbols are growing in popularity in fashion, particularly to maintain the authenticity of their country of origin [37]. The literature also highlights that fashion motivation for ethnic identity plays an important role in explaining purchase intentions and is meaningful for individuals who use it.…”
Section: Fashion Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman and Kharb [36] found that fashion innovativeness is particularly valued by young consumers when purchasing clothing. Furthermore, handcrafted products that incorporate ethnic identities and cultural symbols are growing in popularity in fashion, particularly to maintain the authenticity of their country of origin [37]. The literature also highlights that fashion motivation for ethnic identity plays an important role in explaining purchase intentions and is meaningful for individuals who use it.…”
Section: Fashion Motivationmentioning
confidence: 99%
“…Additionally, Liu et al [84] found that changes in consumer attitudes can affect their purchase intention in clothing consumption. The literature highlights the role of positive attitudes among diversity-seeking consumers and ethnic groups in shaping their responses to products with ethnic orientation [8,37]. It is also suggested that conserving the cultural, social, traditional, and environmental values of ethnically oriented products positively impacts consumers' attitudes.…”
Section: Consumer Attitudesmentioning
confidence: 99%